Evaluasi Antioksidan dan Mutu Kimia Cookies Pegagan (Centella asiatica) dengan Pemanis Stevia (Stevia rebaudiana) - Kintan Nuryantini; Dewi Amrih (Universitas Muhammadiyah Semarang, 2026)
Centella asiatica, or pegagan, is known as a source of natural compounds that have the potential to provide antioxidant activity. The use of pegagan in functional food development can be done by adding pegagan leaf powder to snack products such as cookies. In addition, innovation in cookie formulation can be done by substituting sugar with the natural sweetener stevia (Stevia rebaudiana), which has low calories and is safe for diabetics. This study aims to evaluate the effect of the addition of pegagan powder and the use of stevia sweetener on the antioxidant activity and chemical characteristics of cookies. The study design used a completely randomized design (CRD) with a factorial pattern with varying concentrations of both ingredients tested. Parameters observed included antioxidant activity (DPPH method), reducing sugar content (Nelson-Somogyi method), and water content (thermogravimetric method). The results showed that variations in the addition of pegagan powder and stevia sweetener had a significant effect on reducing sugar and water content, but did not show a significant difference in antioxidant activity. The maximum antioxidant activity was found in cookies fortified with 2.5% pegagan, while the highest reducing sugar content was found in cookies containing 25% stevia. These findings indicate that the combination of these two ingredients plays a role in determining the chemical characteristics of cookies and has the potential to be further developed as a functional food product.